Cortically Evoked Long-Lasting Inhibition of Pallidal Neurons in a Transgenic Mouse Model of Dystonia - Chiken, Satomi (Society for Neuroscience, 2008)
Dystonia is a neurological disorder characterized by sustained or repetitive involuntary muscle contractions and abnormal postures. To understand the pathophysiology of dystonia, neurophysiological analyses were performed on hyperkinetic transgenic mice generated as a model of DYT1 dystonia. Abnormal muscle activity, such as coactivation of agonist and antagonist muscles and sustained muscle activation, was frequently observed in these mice. Recording of neuronal activity in the awake state revealed reduced spontaneous activity with bursts and pauses in both the external and internal segments of the globus pallidus. Motor cortical stimulation evoked responses composed of excitation and subsequent long-lasting inhibition in both pallidal segments, which were never observed in the normal mice. In addition, the somatotopic arrangements in both pallidal segments were disorganized. Long-lasting inhibition induced by cortical inputs in the internal pallidal segment may disinhibit thalamic and cortical activity, resulting in the motor hyperactivity observed in the transgenic mice.